The relationship between terminal duct lobular unit features and mammographic density among Chinese breast cancer patients. Issue 1 (7th January 2019) - Sung, Hyuna; Guo, Changyuan; Li, Erni; Li, Jing; Pfeiffer, Ruth M.; Guida, Jennifer L.; Cora, Renata; Hu, Nan; Deng, Joseph; Figueroa, Jonine D.; Sherman, Mark E.; Gierach, Gretchen L.; et al.
Abstract : Extensive mammographic density (MD), a well‐established breast cancer risk factor, is a radiological representation of stromal and epithelial breast tissue content. In studies conducted predominantly among Caucasian women, histologic measures of reduced terminal duct lobular unit (TDLU) involution have been correlated with extensive MD, but independently associated with breast cancer risk. We therefore examined associations between TDLU measures and MD among Chinese women, a low‐risk population but with high prevalence of dense breasts. Diagnostic pre‐treatment digital mammograms were obtained from 144 breast cancer cases at a tertiary hospital in Beijing and scored using the Breast Imaging Reporting and Data System (BI‐RADS) density classification. TDLU features were assessed using three standardized measures (count/100 mm 2, span [μm], and acini count/TDLU) in benign tissues. Associations between each of TDLU measures and MD were examined using generalized linear models for TDLU count and span and polytomous logistic regression for acini count with adjustment for potential confounders stratified by age. Among women ≥50 years, 63% had dense breasts; cases with dense breasts (BI‐RADS, c‐d) had greater TDLU count (21.1 [SE = 2.70] vs . 9.0 [SE = 1.83]; p = 0.0004), longer span (480.6 μm [SE = 24.6] vs . 393.8 μm [SE = 31.8]; p = 0.03), and greater acini count (ORtrend = 16.1; 95%CI = 4.08–63.1; p trend < 0.0001) compared to those with non‐dense breasts (BI‐RADS, a‐b). Among women <50 years, 91% had dense breasts, precluding our ability to detect associations. Our findings are consistent with previously reported associations between extensive MD and reduced TDLU involution, supporting the hypothesis that breast cancer risk associated with extensive MD may be related to the amount of "at‐risk" epithelium. Abstract : What's new? Women with extensively dense breasts carry a heightened cancer risk, a finding well established in the Caucasian population. Here, the authors confirmed this finding in Chinese women by examining the involution of the aging breast, specifically of the terminal duct lobular unit, in relationship to the mammographic density. This extension to an Asian population underscores the model that a higher amount of "at‐risk" epithelium due to reduced involution link extensive breast density with breast cancer risk.